2020
DOI: 10.1080/08897077.2019.1671940
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Patient-Centered Care and Outcomes in Specialist Drug and Alcohol Treatment: A Systematic Literature Review

Abstract: Background: Patient-centered care is strongly advocated as a key for improving the quality of healthcare. Research examining the impact of patient-centered care in healthcare has concluded that there are demonstrable albeit inconsistent relationships between patient experience, quality of care, and healthcare outcomes. Knowledge of the impact of patient-centered care in the treatment of substance use disorder is limited. The aim of this review was to assess relationships between indicators of patient-centered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 61 publications
2
38
0
1
Order By: Relevance
“…Among people attending treatment for SUDs, unmet physical health needs have been associated with treatment drop-out, increased risk for relapse and reduced quality of life [8,9]. Patientcentred approaches that respond to the diverse needs of problematic AOD use, including physical health, are widely advocated for [10,11] and are recommended within clinical practice guidelines [12,13]. Research on the effectiveness of integrated care for SUDs has focused predominantly on the integration of AOD treatment and mental health care.…”
Section: Introductionmentioning
confidence: 99%
“…Among people attending treatment for SUDs, unmet physical health needs have been associated with treatment drop-out, increased risk for relapse and reduced quality of life [8,9]. Patientcentred approaches that respond to the diverse needs of problematic AOD use, including physical health, are widely advocated for [10,11] and are recommended within clinical practice guidelines [12,13]. Research on the effectiveness of integrated care for SUDs has focused predominantly on the integration of AOD treatment and mental health care.…”
Section: Introductionmentioning
confidence: 99%
“…First, being patient-centered was valued, including allowing patients to explore the menu of options available to them given their individual preferences and needs, providing flexibility in terms of interaction with program staff (eg, telehealth), and choice of moderation vs. abstinence goal. Patient-centered care is a key element of SUD treatment and has been found to improve patient outcomes, 56 , 57 and previous research has found that patients value being involved in decisions about their treatment and having autonomy. 25 Therefore, programs should include training and support to program staff on providing patient-centered care.…”
Section: Discussionmentioning
confidence: 99%
“…Each service offers a range of similar programs that are tailored to local operating guidelines. Research is being undertaken across the six services to consider the role for individual client-focused programs and processes [ 50 ]. From there, a more individual approach could be offered to cater for specific cultural, social and emotional needs of each client.…”
Section: Discussionmentioning
confidence: 99%